Transformation of Arabic Language Learning: Latest Innovations at MTs Negeri 1 Ponorogo to Face 21st Century Challenges - Ratna Utami Nur Ajizah (Tarbawi: Journal of Islamic Education, 2023)
This research aims to describe the latest innovations in Arabic language learning at MTs Negeri 1 Ponorogo Putri, addressing the challenges of the 21st century. It involves Arabic language teachers, students, and school staff. Qualitative research methods, including classroom observation, interviews, and documentation, were used to collect data. The findings reveal that MTs Negeri 1 Ponorogo has implemented various innovations in Arabic language learning. These include the use of information and communication technologies, such as language learning apps, interactive media, and online platforms. Additionally, a teaching approach emphasizing active speaking, listening, reading, and writing skills in Arabic has been adopted. Both teachers and students have provided positive feedback on the benefits of these innovations. The research has significant implications for Arabic language learning development, not only at MTs Negeri 1 Ponorogo but also in other schools. The implemented innovations can serve as examples in addressing 21st-century challenges, such as enhancing digital literacy, preparing students for cross-cultural communication, and equipping them for academic and professional success.